Elucidating Neuronal Mechanisms Using Intracellular Recordings during Behavior. Issue 6 (June 2018) - Lee, Albert K.; Brecht, Michael
Abstract : Intracellular recording allows measurement and perturbation of the membrane potential of identified neurons with sub-millisecond and sub-millivolt precision. This gives intracellular recordings a unique capacity to provide rich information about individual cells (e.g., high-resolution characterization of inputs, outputs, excitability, and structure). Hence, such recordings can elucidate the mechanisms that underlie fundamental phenomena, such as brain state, sparse coding, gating, gain modulation, and learning. Technical developments have increased the range of behaviors during which intracellular recording methods can be employed, such as in freely moving animals and head-fixed animals actively performing tasks, including in virtual environments. Such advances, and the combination of intracellular recordings with genetic and imaging techniques, have enabled investigation of the mechanisms that underlie neural computations during natural and trained behaviors. Highlights: Intracellular recordings allow the input, output, excitability, and structure of a neuron to be assessed. Technical advances have simplified obtaining intracellular recordings from awake brains. Such recordings can elucidate the mechanisms underlying brain states, sparse coding, gain control, and learning.